Awake airway endoscopy in mucopolysaccharidosis: a case report - Sofia Fernandes; Jo.·o Borges; Marta Martins (Brazilian Journal of Anesthesiology, 2023)
Mucopolysaccharidosis (MPS) are a group of rare genetic inherited diseases with a progressive course due to the accumulation of glycosaminoglycans resulting in anatomic abnormalities and organ dysfunction, including the respiratory, cardiovascular, skeletal, and neurological systems that can increase the risk of anesthesia complications. Clinical manifestations are variable, multisystemic, and include severe morphological changes. The anesthetic management of these patients is complex, particularly airway management, which can be planned to include a fiberoptic airway investigation prior to surgery. We present two cases of patients with MPS type VI and VII who underwent fiberoptic airway mapping under conscious sedation, with no complications. Since MPS is a rare but challenging disease concerning the airway management, we propose a safe and effective anesthetic technique that could be used for fiberoptic bronchoscopy and allow fiberoptic-assisted tracheal intubation at the time of surgery.